Durable T cell immunity to COVID-19 vaccines in MS patients on B cell depletion therapy - Julia Davis-Porada; Ceren Tozlu; Claudia Aiello; Sokratis A. Apostolidis; Amit Bar-Or; Riley Bove; Diego A. Espinoza; Sugeidy Ferreira Brito; Dina Jacobs; Mihir Kakara; Kaho Onomichi; Adelle Ricci; et al. (npj Vaccines)
Abstract Immune-mediated protection generated to COVID-19 mRNA vaccines is associated with anti-Spike (S) protein neutralizing antibodies. However, humoral immunity is compromised in B cell depleting (BCD) therapies, used to treat autoimmune diseases such as Multiple Sclerosis (MS). To study the effect of BCD on the durability and protective efficacy of vaccine-induced immunity, we evaluated S-reactive antibodies and T cell responses 1–70 weeks post-vaccination in MS cohorts treated with BCD compared to non-BCD therapies from four centers. BCD-treated participants had significantly reduced antibody levels and enhanced frequencies of S-reactive CD4+ and CD8+ memory T cells to COVID-19 vaccination compared to the non-BCD group, with some variations among different BCD formulations. T cell memory responses persisted up to 14 months post-vaccination in both BCD and non-BCD cohorts, who experienced similar clinical protection from COVID-19. Together, our results establish a critical role for T cell-mediated immunity in anti-viral protection independent of humoral immunity.